The PENOLAKAN TERHADAP HASIL PENGKURAN ARAH KIBLAT DALAM PERSPEKTIF MAQASID AS-SYARI’AH - Nur'aini (UIN ALAUDDIN MAKASSAR, 2022)
In 2006 the Ministry of Religion held a Qibla direction certification program for all mosques in Indonesia as an effort to provide peace and stability in worship. However, in practice, after knowing the results of the new measurements, the mosque takmirs refused to apply them in the prayers. This is done with the reason to maintain the brotherhood of the mosque congregation. The results of this study indicate that the phenomenon of rejecting the direction of the Qibla in the maqashid sharia perspective is better than forcing the community to implement something new, which can cause damage to community unity. Because maintaining unity and integrity is part of the maqasid sharia of an Islamic law.